Dietary supplementation with hydroxy-methionine manganese improves meat quality, antioxidant capacity, and lipid metabolism in Cherry Valley ducks (Anas platyrhynchos domesticus) - Liu, Yang; Hou, Qinteng; Chang, Yaqi; Xie, Yueqin; Zhao, Hua; Chen, Xiaoling; Liu, Guangmang; Tang, Jiayong; Tian, Gang; Cai, Jingyi; Jia, Gang (Frontiers in Veterinary Science, 2025)
Hydroxymethionine manganese (MnHMet), as a novel organic trace element additive, has demonstrated significant effects on improving meat quality, enhancing antioxidant capacity, and lipid metabolism. However, its specific effects on Cherry Valley ducks remain unclear. This study explored the effects of dietary MnHMet on meat quality, antioxidant capacity, and lipid metabolism in meat ducks. In a 35-day study, 560 1-day-old male ducks were randomly assigned to seven groups: six groups were supplemented MnHMet at 0, 30, 60, 90, 120, and 150 mg/kg, and a group was supplemented 120 mg/kg MnSO4. Results showed that the 120 mg/kg MnHMet group had significantly lower triglyceride (TG) levels than the MnSO4 group (P < 0.05). Serum high-density lipoprotein cholesterol levels increased significantly in the MnHMet groups compared to the 0 mg/kg group and showed a quadratic change to increasing MnHMet levels (P < 0.05). MnHMet supplementation reduced drip loss, shear force, abdominal fat weight, and percentage while increasing intramuscular fat (IMF, P < 0.05). Drip loss and shear force decreased linearly, and IMF showed a quadratic response to MnHMet levels (P < 0.05). Fatty acid analysis revealed a quadratic decrease in hepatic C23:0 concentrations (P < 0.05). MnHMet improved antioxidant capacity by enhancing total antioxidant capacity (T-AOC), upregulating MnSOD mRNA expression in the liver and breast muscle, increasing hepatic MnSOD levels, and reducing malondialdehyde (MDA) levels (P < 0.05). T-AOC levels exhibited quadratic and linear increases in breast muscle and liver, respectively, while hepatic MDA levels decreased quadratically (P < 0.05). Catalase levels in breast muscle were significantly higher in the MnHMet group than in the MnSO4 group (P < 0.05). Additionally, MnHMet reduced adipocyte area, downregulated hepatic fatty acid synthase and acetyl-CoA carboxylase, and upregulated peroxisome proliferator-activated receptor-γ, carnitine palmitoyltransferase-1α, and lipoprotein lipase (P < 0.05). Based on IMF and abdominal fat percentage, the optimal MnHMet supplementation levels were 107.5 and 117.5 mg/kg, respectively. These results revealed that MnHMet supplementation improved muscle mass, fatty acid composition, reduced abdominal fat, and enhanced meat quality by regulating antioxidant capacity and lipid metabolism in meat ducks.